WOMEN'S POLITICAL REPRESENTATION IN THE GERINDRA PARTY FACTION OF THE CENTRAL JAVA LEGISLATURE: AN ANALYSIS OF AFFIRMATIVE ACTION POLICIES AND THE OBSTACLES FACED - Salsabila, Thouf; Widigda , Yoga; Ulfah , Early Juliana; Sari , Adeliya Rahma (Forum Ilmu Sosial, 2025)
Women face challenges to enter the realm of power as long as the concept of power continues to be associated with masculine traits. The phenomenon of limited space for women in political party structures cannot be interpreted simply as a quantitative issue of the number of representation, but rather a manifestation of more fundamental power relations in the Indonesian political system. This research uses a qualitative approach with descriptive research methods to seek deeper information about affirmative action, political representation and the politics of presence, as well as the obstacles and constraints of women in the Gerindra Party Faction Central Java. The results shows that Gerindra Party has implemented a number of policies and strategic steps that encourage women to be active in politics. However, although Gerindra Party provides equal opportunities for women, there are still challenges that need to be overcome. While there are still challenges that need to be overcome, the party’s efforts should be applauded as part of a broader struggle to create a system of gender equality in.